Detection of Mycoplasma pneumoniae in Simulated and True Clinical Throat Swab Specimens by Nanorod Array-Surface-Enhanced Raman Spectroscopy - Hennigan, Suzanne L. (Public Library of Science, 2010)
The prokaryote Mycoplasma pneumoniae is a major cause of respiratory disease in humans, accounting for 20% of all community-acquired pneumonia and the leading cause of pneumonia in older children and young adults. The limitations of existing options for mycoplasma diagnosis highlight a critical need for a new detection platform with high sensitivity, specificity, and expediency. Here we evaluated silver nanorod arrays (NA) as a biosensing platform for detection and differentiation of M. pneumoniae in culture and in spiked and true clinical throat swab samples by surface-enhanced Raman spectroscopy (SERS). Three M. pneumoniae strains were reproducibly differentiated by NA-SERS with 95%–100% specificity and 94–100% sensitivity, and with a lower detection limit exceeding standard PCR. Analysis of throat swab samples spiked with M. pneumoniae yielded detection in a complex, clinically relevant background with >90% accuracy and high sensitivity. In addition, NA-SERS correctly classified with >97% accuracy, ten true clinical throat swab samples previously established by real-time PCR and culture to be positive or negative for M. pneumoniae. Our findings suggest that the unique biochemical specificity of Raman spectroscopy, combined with reproducible spectral enhancement by silver NA, holds great promise as a superior platform for rapid and sensitive detection and identification of M. pneumoniae, with potential for point-of-care application.